Leveraging AI (Chatgpt) for English Language Learning: Potential, Challenges, And Future Directions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study critically investigates the pedagogical potential of ChatGPT in English language learning. As AI-powered conversational agents become increasingly integrated into educational environments, ChatGPT presents an opportunity for language learners to engage in interactive, personalized, and accessible instruction. This paper evaluates the model's contributions to developing core language skills, including grammar, vocabulary, writing, and speaking. Using a mixed-methods approach, the study collects data from learners and educators worldwide, analyzing patterns of AI use, perceived benefits, and pedagogical challenges. The findings reveal both the transformative potential and inherent limitations of AI tools, particularly in areas such as cultural nuance, critical thinking, and over-reliance. The discussion advocates for a hybrid instructional framework that integrates AI technologies with guided human facilitation and digital literacy.